Antibody genes and diversity - Clark, Mike (Henry Stewart Talks, 2021)
Mammalian antibody classes, Structure of antibodies, Antibody variation, Mechanisms that elevate the variability of antibodies, B cell differentiation, division and somatic hypermutation, The T-cell antigen receptor complex, TCR chains are analogous to Ig H & L chains